The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/07481187.2014.885469
|View full text |Cite
|
Sign up to set email alerts
|

Existential Threat or Dissociative Response? Examining Defensive Avoidance of Point-of-Care Testing Devices Through a Terror Management Theory Framework

Abstract: Using a terror management theory framework, this study investigated if providing mortality reminders or self-esteem threats would lead participants to exhibit avoidant responses toward a point-of-care testing device for cardiovascular disease risk and if the nature of the device served to diminish the existential threat of cardiovascular disease. One hundred and twelve participants aged 40-55 years completed an experimental questionnaire. Findings indicated that participants were not existentially threatened b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Building on the work of Ernest Becker (1973) the theory suggests that people seek to dispel their terror by pursuing feelings of symbolic immortality; that is, because one's culture can exist long after one's individual death, people can become imbued with the potential immortality that is inherent in their cultures by either bolstering their cultural worldview or by viewing themselves as living up to the standards of their cultures. People can achieve feelings of symbolic immortality by engaging in a variety of symbolic acts, such as investing in one's national identity (Greenberg, Pyszczynski, Solomon, Simon, & Breus, 1994), donating to charity (Dunne, Gallagher, & Matthews, 2015;Jonas, Schimel, Greenberg, & Pyszczynski, 2002), derogating members of other religious groups (Vail, Courtney, & Arndt, 2019), or punishing people who are breaking the laws (Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989).…”
Section: Managing the Terror Of Publication Bias: A Comprehensive P-curve Analysis Of The Terrormentioning
confidence: 99%
“…Building on the work of Ernest Becker (1973) the theory suggests that people seek to dispel their terror by pursuing feelings of symbolic immortality; that is, because one's culture can exist long after one's individual death, people can become imbued with the potential immortality that is inherent in their cultures by either bolstering their cultural worldview or by viewing themselves as living up to the standards of their cultures. People can achieve feelings of symbolic immortality by engaging in a variety of symbolic acts, such as investing in one's national identity (Greenberg, Pyszczynski, Solomon, Simon, & Breus, 1994), donating to charity (Dunne, Gallagher, & Matthews, 2015;Jonas, Schimel, Greenberg, & Pyszczynski, 2002), derogating members of other religious groups (Vail, Courtney, & Arndt, 2019), or punishing people who are breaking the laws (Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989).…”
Section: Managing the Terror Of Publication Bias: A Comprehensive P-curve Analysis Of The Terrormentioning
confidence: 99%
“…Two external experts in qualitative analysis, acting as triangulation researchers, then reviewed the code generation, the results obtained and the data analysis performed (Denzin, 1989;Flick, 1992). EMOTIONS AROUSED BY THOUGHTS ABOUT ONE'S OWN DEATH Emotions: Nouns that participants have used to describe what they feel thinking about their own death.…”
Section: Discussionmentioning
confidence: 99%
“…While TMT is premised on the supposition that the fear of death is universal, cross-cultural studies indicates a mixed response. Research indicated that many cultures (e.g., Ireland, India, and Iran) treat death with attitudes other than fear, such as acceptance and contempt (Dunne, Gallagher, and Matthews 2015; Fernandez, Castano, and Singh 2010). Therefore, multinational studies should be prioritized to validate TMT in a diverse population.…”
Section: Literature Reviewmentioning
confidence: 99%